The alternative lengthening of telomeres mechanism jeopardizes telomere integrity if not properly restricted - Silva, Bruno (2022)
Copyright © 2022 the Author(s). Published by PNAS. This open access article is distributed under Creative Commons Attribution License 4.0 (CC BY).